The Relationship of Hot Work Climate on Physiological Response in Traditional Clover Leaf Oil Refining Workers - Yuniarti, Lucia Ni Luh; Saputra, I Kadek Dwi Arta; Pemayun, Cokorde Gde Putra; Sudiarta, I Ketut (Journal of Language and Health, 2024)
In the clove leaf oil refining process which uses steam, it produces a hot temperature residue which affects clove leaf oil refinery workers. Exposure to a hot working climate can have an impact on human physiological responses such as an increase in body temperature, pulse rate, blood pressure and weight loss. as a result of producing quite a lot of sweat fluid. This research aims to investigate the physiological responses of clove leaf oil refinery workers to exposure to a hot working climate. In the clove leaf oil refining process, which utilizes steam, the production of hot temperature residue affects the workers. Exposure to such conditions can lead to various physiological responses, including increased body temperature, pulse rate, blood pressure, and weight loss due to significant sweating. Employing a quantitative research design with a cross-sectional analytical approach, data were collected from all 22 workers using a total sampling technique. The primary data collected were subjected to analysis using paired simple t-tests and the Pearson correlation test to explore relationships between variables. The findings reveal significant increases in physiological responses post-work, including elevated body temperature, pulse rate, systolic and diastolic blood pressure, and a reduction in body weight. The obtained p-values for all variables were <0.05, indicating statistically significant differences between pre-work and post-work conditions. Furthermore, the Pearson correlation test analysis between heat stress data and post-work physiological responses, including body temperature, pulse rate, systolic and diastolic blood pressure, as well as body weight, revealed moderate to strong correlations (r). These results underscore the detrimental impact of hot working climates on the physiological well-being of clove leaf oil refinery workers. Such findings highlight the urgent need for implementing appropriate measures to mitigate heat-related health risks in occupational settings, safeguarding the health and safety of workers.